Effect of the development stage of the follicular wave on ovarian response, and rate of recovery and quality of embryos in alpacas - Ascencio S., Josías (2019)
The effect of the stage of development of the follicular wave (growth phase, static and regression of the dominant follicle) prior to the natural mounting on the ovulation rate, and the recovery rate and embryo quality in alpacas was evaluated. It was used 51 female alpacas with presence of dominant follicle greater than or equal to 7 mm, which were synchronized with a GnRH analogue. The groups were T1 (n=16): growth phase; T2 (n=19): Static phase and T3 (n=18): Regression phase. The day of the copula was considered as day 0. Ultrasonographic evaluations were conducted on day 2 (occurrence of ovulation) and on day 7 (to measure the size of the corpus luteum). The embryo recovering was done 7 days after the service. Two animals of T1 did not ovulate. There were no significant differences between groups by size of the dominant follicle at the time of service, ovulation rate or size of the corpus luteum on the day of embryo recover. In 52.9% (n=27) of the alpacas, 27 embryos were recovered without significant differences between treatments; however, the embryos of T1 and T2 were of better quality than those of T3 (p<0.05).